Selective Glycerol-to-glycerate Electro-oxidation on Cerium-modified Pt/C Nanocatalyst in an Alkaline Direct Alcohol Fuel Cell: Cogeneration of Energy and Value-added Products - Cursi, Fabiano S.; Grimaud, Laurie; Rousseau, Julie; Servat, Karine; Morais, Cláudia; Napporn, Teko W.; de Andrade, Adalgisa R. [UNESP]; Kokoh, K. Boniface (Wiley, 2024)
Glycerol electro-oxidation reaction was performed in an alkaline environment with an anion exchange membrane fuel cell (AEMFC) operating in bath mode at low Pt-loadings. BAE-synthesized Pt/C and PtCe/C nanostructured catalysts were used as anode materials during 4-hour operation to selectively obtain 65 % and 41 % of glycerate as main product, respectively. The modification of Pt with Ce improved the catalytic activity of the Pt/C catalyst generating 30 % more energy density after 4-hour operation by achieving a higher degree of glycerol oxidation in cogeneration with added-value products confirmed by spectroelectrochemical (in situ FTIR) and liquid chromatography coupled with mass spectrometry (LC–MS) analyses. The bifunctional mechanism generated by the presence of Ce is used to explain the improvement in the catalytic activity of Pt/C, due to the properties of this rare earth element to adsorb oxygenated species (OH−) and promote oxidation. The cathode material was a polyol-synthesized PdFe/C electro-catalyst for ORR that presented impressive stability and tolerance to glycerol.
Keywords: alkaline direct glycerol fuel cell; cerium; glycerol electro-oxidation; glycerol valorization; Pt-based materials